PENINGKATAN KEMAMPUAN MENULIS TEKS PIDATO DALAM PEMBELAJARAN KETERAMPILAN MENULIS MELALUI MEDIA BERBASIS AUDIO - Bambang Hidayat (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
Abstract: This research is motivated by the still level of the students ability to write text to speech. Tenth grade high school students 20 Palembang country through learning by using audio-based media?.In order to answer the problem formulation.This type of research (PTK). This study was conducted over two cycles each cycle condisting of four components: planning, implements, observation and reflection. The ability to write text to speech through audio-based media experience significant from one cycle to cycle two minimum completeness criteria (KKN) which has ben set at 75. The cycle of the 1941, average values obtained in cycle 65 while the two accumulated value of learning outcomes in 2339, the average 78. Based on the acquisition value of the second cycle there is an increasing and developing students abilities from oneth cycle to cycle two, the cycle of the two cycle average of 64.70%, average of 77.97%.